Exploring Kenyan Women University Students’ Everyday Interaction with Information - Shannon, Brooke (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
A social constructionist methodology was used to explore how Kenyan women university students interact with information in everyday life. Focus was on how participants interpret experiences within the historical, cultural, and material spaces they inhabit. Methods used were linguistics pragmatics, phenomenology, and hermeneutics. Conceptual implications for information literacy are discussed. Une méthodologie sociale constructioniste est utilisée pour explorer comment les étudiantes universitaires kenyanes interagissent avec l’information au quotidien. Nous avons insisté sur les façons dont les participantes interprètent leurs expériences dans les espaces historiques, culturels et matériels où elles habitent. Les méthodologies utilisées comprennent la pragmatique linguistique, la phénoménologie et l’herméneutique. Nous discutons finalement de leurs implications sur la maîtrise de l’information.